Optimalisasi Pemberian Tunjangan Melalui Implementasi Sistem E-Kinerja di Dinas Ketahanan Pangan dan Pertanian Kabupaten Nias Utara - Gea, Junianiwarni; Waruwu, Meiman Hidayat; Bate’e, Maria Magdalena; Zega, Yamolala (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to explore the optimization of allowance distribution through the implementation of the E-Kinerja system at the Department of Food Security and Agriculture of North Nias Regency. E-Kinerja is a technology-based performance evaluation system implemented to improve transparency and accountability in employee performance assessments. The research findings indicate that the implementation of E-Kinerja can enhance fairness in allowance distribution through more objective and measurable evaluations. However, the study also identifies challenges related to budget constraints and infrastructure limitations that need to be addressed to achieve the desired optimization.